Development, Characterization, and Evaluation of Hydrogels from Natural Resources for Ammonium Adsorption - Dietrich, Justo; Bonanni, Sebastián; Gonzalez, Jimena S. (Fine Chemical Engineering, 2025)
Due to its simplicity and low cost, biological nitrification in fixed bed biofilters followed by denitrification is one of the most applied approaches for the removal of ammonia from wastewater. However, traditional filling materials of biofilters, such as sand, gravel, and clay, have limited water adsorption capacities (10% to 25% by volume), which restricts the treatment capacity. Besides, the high weight of these materials increases construction labor. This study explores the potential of hydrogels as an alternative to conventional biofilter materials. Hydrogels can be formed from natural polymers like alginate and starch and possess high water retention properties and biodegradability, making them suitable for adsorbing contaminants and immobilizing microorganisms to enhance biological wastewater treatment processes. The incorporation of clay into the system is also investigated for its potential to improve mechanical and adsorption properties. The performance of these hydrogels for ammonium removal was evaluated using spectroscopic, gravimetric, and microscopic techniques in experimental-scale systems. The findings aim to provide insights into developing effective, eco-friendly solutions for traditional wastewater treatment systems.